Distribution of ABO and Blood Groups among various Caste and Ethnic Groups – A cross-sectional Hospital Based Study in a Teaching Hospital of Western Nepal - Thapa, Sushma; Ghosh, Arnab; Ghartimagar, Dilasma; Regmi, Sudeep; Jhunjhunwala, Adarsh (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Red blood cells contain antigens on its membrane which are inherited according to Mendelian Law. Despite the identification of more than 400 red blood cell antigens, ABO and Rhesus blood group systems are clinically most significant. The current study aimed at determining the distribution of blood groups among different caste and ethnic groups of Western Nepal. Methods: A descriptive cross-sectional study conducted among individuals in the Blood Bank of Department of Pathology of a Teaching Hospital from January 2018 to July 2019. Ethical approval was taken from the Institutional Review Committee (Ref. 384). Convenient sampling was done. Data were entered in Microsoft Excel and analysed using Statistical Package for the Social Sciences version 21.0. Point estimate at 95% Confidence Interval was calculated along with frequency and proportion for binary data. Results: In ABO system, the frequency of O, A, B and AB blood groups were found to be 960(33.9%) (95% Confidence Interval= 32.15-35.64), 930(32.8%) (95% Confidence Interval= 31.11-34.57), 716(25.3%) (95% Confidence Interval= 23.68-26.88) and 226(8.0%) (95% Confidence Interval=6.98-8.98) respectively. Rh positive was the dominant Rhesus blood group, 2758(97.4%) (95% Confidence Interval=96.73-97.94). Blood group O was dominant in Brahmin, Bishwakarma, Gurung, Pariyar, Tamang, Terai Brahmin and Limbu. Conclusions: The frequency distribution pattern of ABO blood group was observed as blood group O>A>B>AB. Variation in the blood group distribution was observed in different ethnic groups.